Experiencia de implementación de una política de Gestión de Empleo Local en una Unidad Minera de Orcopampa, Castilla, Arequipa, 2015 -2018 - Flores Solis, Analy Vanessa (2024)
This research work focuses on the analysis of the social and labor impact generated by the implementation of a Local Employment System, in the community of Orcopampa in the province of Arequipa, in the region of Castilla. The purpose of this study is to collect the perception of the actors and the factors that had an impact due to its implementation. Incorporating the social factor into the selection procedure led the community to adopt an active role and with this a new relationship and participation model was created. To carry out the analysis, a qualitative investigation proposed, which collected information from both the participating actors of the company and the community, about indicators of business and community development that changed since the implementation of the procedure. In the findings found in the work, it recognized that the local Employment System generated greater access to decent work, but did not improve any other indicator of population development. The perception of the company and the perception of the community members was positive since, thanks to the joint work and the participation of the community, greater accessibility to work in the area was generate. "Work is no longer a favor" expression of one of the community members of the area, where it is recognized that a mechanism has been created by the company, which respects the prioritization of local hiring and where the community member assumes responsibility for their selection process itself.